Characterizing misbehaviour among Jordanian high school students - Mahasneh, Ameen Mohammed Mousa; Md Nor, Sharifah; Md. Aroff, Abdul Rahman; Abdullah, Nur Surayyah Madhubala; Abu Samah, Bahaman; Mahasneh, Ahmad Mohammed Mousa (Canadian Center of Science and Education, 2011)
The main purpose of this paper is to investigate the level of student misbehaviour and to explore the types of student misbehaviour among Jordanian high school students in the Governorate of Jarash. This paper presents the findings of a survey conducted to identify the level and type of misbehaviour. It emphasizes the important role school plays in reinforcing positive societal norms and values in teenagers with the ultimate aim to produce well-adjusted young adults. The findings support the idea that factors such as gender and grade level affect the type and level of misbehaviour exhibited by Jordanian high school students. The results of this study also revealed that the majority of the respondents showed a low level of misbehaviour. The most frequent types of misbehaviour found among Jordanian high schools students were disobedience, classroom disruption and vandalizing school property. Student misbehaviour differs significantly according to the students’ gender, grade level and the type of school they attend.